Analysis of Hematologic Parameters and Serum Bilirubin Levels in Complicated and Uncomplicated Acute Appendicitis Patients - Rini Rahman; Ani Kartini; Yuyun Widaningsih; Agus Alim Abdullah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Acute appendicitis is inflammation of the vermiformis appendix due to lumen obstruction followed by bacterial infection. Acute appendicitis is classified into two types of disease, namely complicated and uncomplicated. Acute inflammation of the appendix requires immediate surgical action to prevent complications; therefore, a further laboratory test is required. This study was retrospective research which analyzed several hematologic parameters (WBC, Neutrophils, NLR, RDW, PLTMPV, PDW) and serum bilirubin levels. Data were statistically analyzed using Independent-t and Mann-Whitney test. Univariate logistic regression test was used to evaluate the correlation of hematologic parameters and significant serum bilirubin levels with the diagnosis of complicated and uncomplicated appendicitis. The cut-off value and diagnosis value were measured using Receiver Operating Characteristic (ROC) curve analysis. This study involved 173 subjects categorized into 67 complicated and 106 uncomplicated acute appendicitis patients. Whole blood count and neutrophil counts were significantly higher in complicated acute appendicitis (p <0.05). Similarly, NLR and PLT were significantly higher in complicated acute appendicitis (p <0.001), p > 0.05 was obtained in RDW-CV, MPV and PDW values. The higher serum bilirubin levels were reported in patients with complicated acute appendicitis compared to uncomplicated acute appendicitis (p <0.001). Logistic regression test results showed significant PLT parameters with p <0.001, while there was no significance of hematologic parameters such as WBC, neutrophil, NLR, RDW-CV, MPV, PDW and bilirubin levels. Area under curve results on the ROC curve showed 74.4% PLT with sensitivity and specificity of 97.17% and 40.29%, respectively. From the analysis of hematologic parameters and measurement of serum bilirubin levels, only the PLT parameter can be used as one of the parameters for the diagnosis of complicated appendicitis with high sensitivity but low specificity. It was recommended to perform prospective studies with more subjects.